Incidents in Corporate Social Responsibility as a consequence of the supply of fertilizers of Russian origin in Latin American markets - Bolaños-Silva, Luis G. (EFIM Ediciones, 2023)
This article examines corporate social responsibility (CSR) issues arising from the sourcing of Russian-origin fertilisers in Latin American markets, despite the sanctions imposed on this country by the international community. CSR refers to the business practice of considering for the social, environmental, and ethical impacts of a company's operations and taking responsibility for those impacts. In the context of the current supply of Russian-origin fertilisers, concerns are raised re-garding to social responsibility, ethics, and transparency. In addition, the dependence and security of agricultural supply in relation to Russian fertilisers imports is examined. This study seeks to identify the challenges and implications of Russian fertilisers supply practices in Latin American markets in terms of CSR, in order to foster greater awareness of the potential issues that this could generate and promote more responsible practices in the agricultural industry.